Modal Intelektual, Budaya Perusahaan dan Kinerja Keuangan pada Sektor Perbankan Indonesia - Dahyang Ika Leni Wijayani; Aditya Achmad Rakim; Dian Saripujiana; Hasto Finanto (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
This study examines whether intellectual capital and corporate culture affects financial performance in Indonesia. Data are drawn form 34 sample of publicly bank that listed in Indonesia Stock Exchange (IDX). Intellectual capital using VAIC method and the four type of corporate culture (collaboration oriented/COL, control oriented/CON, competition oriented/COM, dan creation oriented) using ATLAS.ti  following the bag of words by Fiordelisi & Ricci (2014). We find evidence that intellectual capital, collaboration oriented - culture (COL),  creation – oriented culture (CRE) are positevely related to financial performance. Competition – oriented culture (COM) is negatively related to financial performance, while the last type of corporate culture:  control – oriented culture (CON) is not relayed to financial performance.